Evaluation of diet complexity and benzoic acid on growth performance of nursery pigs - J E Nemechek; Michael D Tokach; Steven S Dritz; Robert D Goodband; Joel M DeRouchey; J R Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 280 weanling pigs (PIC 327 × 1050, initially 15.4 lb, 3 d postweaning) were used in a 28-d trial to evaluate the effects of benzoic acid and diet complexity on growth performance. Treatments were arranged as a 2 × 2 factorial with 2 diet complexities and 2 benzoic acid levels (0 vs. 0.5%) fed for the first 14 d. Diet complexity treatments were either a simple diet that did not contain any lactose, zinc oxide, or specialty protein sources or a complex diet that contained 10% dried whey, 1.25% select menhaden fish meal, 1.25% spray-dried blood cells, and 0.25% zinc oxide. From d 14 to 28, pigs were fed a common diet with and without 0.5% benzoic acid, with pigs continuing to receive benzoic acid if they received it from d 0 to 14. No growth performance interactions (P>0.33) were detected between diet complexity and benzoic acid. From d 0 to 14, when different diet complexities were fed, pigs fed simple diets had decreased (P<0.001) ADG and ADFI and poorer (P<0.001) F/G compared with pigs fed complex diets. From d 14 to 28, pigs previously fed simple diets showed compensatory growth and tended to have increased (P<0.06) ADG and improved (P<0.003) F/G compared with pigs previously fed the complex diets. Overall (d 0 to 28), pigs fed simple diets during Phase 1 had decreased (P<0.001) ADG and ADFI from d 0 to 28 compared with pigs fed complex diets. For the main effect of benzoic acid, no differences (P>0.10) were observed in ADG, ADFI, or F/G. In conclusion, as expected, early nursery pig growth performance was reduced when pigs were fed simple diets. Benzoic acid had no impact on pig growth performance regardless of diet complexity.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Benzoic acid; Diet complexity; Nursery pig